Knockdown of BC200 RNA expression reduces cell migration and invasion by destabilizing mRNA for calcium-binding protein S100A11. Issue 10 (3rd October 2017) - Shin, Heegwon; Lee, Jungmin; Kim, Youngmi; Jang, Seonghui; Lee, Yunhee; Kim, Semi; Lee, Younghoon
ABSTRACT: Although BC200 RNA is best known as a neuron-specific non-coding RNA, it is overexpressed in various cancer cells. BC200 RNA was recently shown to contribute to metastasis in several cancer cell lines, but the underlying mechanism was not understood in detail. To examine this mechanism, we knocked down BC200 RNA in cancer cells, which overexpress the RNA, and examined cell motility, profiling of ribosome footprints, and the correlation between cell motility changes and genes exhibiting altered ribosome profiles. We found that BC200 RNA knockdown reduced cell migration and invasion, suggesting that BC200 RNA promotes cell motility. Our ribosome profiling analysis identified 29 genes whose ribosomal occupations were altered more than 2-fold by BC200 RNA knockdown. Many (> 30%) of them were directly or indirectly related to cancer progression. Among them, we focused on S100A11 (which showed a reduced ribosome footprint) because its expression was previously shown to increase cellular motility. S100A11 was decreased at both the mRNA and protein levels following knockdown of BC200 RNA. An actinomycin-chase experiment showed that BC200 RNA knockdown significantly decreased the stability of the S100A11 mRNA without changing its transcription rate, suggesting that the downregulation of S100A11 was mainly caused by destabilization of its mRNA. Finally, we showed that the BC200 RNA-knockdown-induced decrease in cell motility was mainly mediated by S100A11. Together, our results show that BC200 RNA promotes cell motility by stabilizing S100A11 transcripts.